Fifteen Coagulation and Fibrinolysis Parameters in Diabetes Mellitus and in Patients with Vasculopathy - Christe, M; Fritschi, J; Lämmle, B; Tran, T H; Marbet, G A; Berger, W; Duckert, F (Thrombosis and Haemostasis, 1984)
Fifteen haemostasis parameters have been measured in 48 normal persons, 36 diabetics without and 44 with complications and 27 with peripheral arterial disease. Since the patients groups are older than normals, part of the differences are due to age. However, the differences are significant between normals and patients. They become highly significant for the diabetics with complications and nephropathy (Table 7). In diabetics without complications factor VIII functions, fibrinogen and thrombin time are related to age whereas there is a negative correlation for the fibrinolytic activity and antithrombin III. The diabetic complications shade off the correlations, which subsist only for VIIIR: CoF, VIIIR: Ag, ATIII and lysis before stasis. With Hbalc as dependent variable VIIIR:CoF is the only significant predictor variable in diabetics (Table 9).
Keywords: Diabetes mellitus; Coagulation; Fibrinolysis; Nephropathy; Vasculopathy